2014
DOI: 10.1111/1751-2980.12179
|View full text |Cite
|
Sign up to set email alerts
|

Four types of Bifidobacteria trigger autophagy response in intestinal epithelial cells

Abstract: Bifidobacteria initiate autophagy activation in IEC. The Atg12-Atg5-Atg16 multimeric complex might participate in the activation of Bifidobacteria-induced cell autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 45 publications
(100 reference statements)
0
16
0
1
Order By: Relevance
“…These include effects by the microbiota on autophagy (Lin et al, 2014), a cellular recycling process that is genetically linked to PD risk, and when impaired may lead to reduced clearance of αSyn aggregates (Beilina and Cookson, 2015; Nalls et al, 2014). Additionally, intestinal bacteria have been shown to modulate proteasome function (Cleynen et al, 2014), which may also aid in the clearance of αSyn inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These include effects by the microbiota on autophagy (Lin et al, 2014), a cellular recycling process that is genetically linked to PD risk, and when impaired may lead to reduced clearance of αSyn aggregates (Beilina and Cookson, 2015; Nalls et al, 2014). Additionally, intestinal bacteria have been shown to modulate proteasome function (Cleynen et al, 2014), which may also aid in the clearance of αSyn inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Irving et al (2014) demonstrated that peptidoglycan derived from Helicobacter pylori and Pseudomonas aeruginosa promotes autophagy in epithelial cells via NOD1 receptor activation. Moreover, several studies reported potential of some Bifidobacteria and Lactobacillus species to stimulate or suppress autophagy (Wu et al, 2013; Lin et al, 2014; Motevaseli et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, single nucleotide polymorphisms (SNPs) within two autophagy-related genes, autophagy-related 16-like 1 (ATG16L1) and the immunity-related GTPase family M (IRGM), are important loci for IBD pathogenesis [12,13]. Dysfunction of these autophagy-related proteins is associated with survival of intracellular bacteria, pro-inflammatory cytokine secretion, and colitis onset [12,14]. Thus, controlling how autophagy is regulated might be a critical strategy for IBD prevention and therapy.…”
Section: Introductionmentioning
confidence: 99%